Alamat ng langaw The legend of the fly - Matias, Segundo D. (Lampara books, 2012)
"In the old days, there was a king who had a rather bad habit. Aside from being arrogant, King Lang-ao was very hard to please when it came to food. He was gluttonous, choosy, wasteful, and he never wanted any dish served twice. Because of this, his loyal cook got angry and cursed him. Bathala and the other cook gods and goddesses quickly responded and the curse immediately took effect. King Lang-ao became a..."